PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Karyawan PT Timbul Jaya Motor Boyolali) - Purwaningsih, Reza Retma; Wahyudi, Amin; Widajanti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
This study aims to determine the significant influence between: (1)Leadership on job satisfaction; (2) The work environment for job satisfaction; (3) Leadership towards performance; (4) Work environment on performance; (5) Job satisfaction on performance; (6) Job satisfaction mediates the effect of leadership on performance; (7) Job satisfaction mediates the effect of the work environment on performance.The population of PT Timbul Jaya Motor Boyolali employees in 2019 is 125 people. Samples were taken in total sampling of 125 people. Data collection techniques using a questionnaire through the test of validity and reliability. The analysis technique uses multiple linear regression with the classic assumption test. The technique of gathering the data is using inquiry sheet validity test and reliability test. The analysis technique uses double regression with classical assumption. Conclusion of research results; (1) The hypothesis which states there is a significant influence of leadership on job satisfaction is verified; (2) The hypothesis which states there is a significant influence of the work environment on job satisfaction is verified; (3) The hypothesis that there is a significant influence of leadership on performance is verified; (4) The hypothesis that there is a significant influence of the work environment on performance is verified; (5) The hypothesis that there is a significant effect of job satisfaction on performance is verified; (6) The hypothesis that there is a significant influence of leadership on performance through job satisfaction is verified; (7) The hypothesis which states there is a significant influence of the work environment on performance through job satisfaction is verified.